Premature ovarian insufficiency: an International Menopause Society White Paper. (2nd September 2020) - Panay, N.; Anderson, R. A.; Nappi, R. E.; Vincent, A. J.; Vujovic, S.; Webber, L.; Wolfman, W.
Abstract: The aim of this International Menopause Society White Paper on premature ovarian insufficiency (POI) is to provide the latest information regarding this distressing condition. The impact of POI has far-reaching consequences due to its impact on general, psychological, and sexual quality of life, fertility prospects, and long-term bone, cardiovascular, and cognitive health. Progress in fully understanding the etiology, diagnosis, and optimal management options has been slow thus far due to the complexity of the condition and fragmented research. Recent advances in epidemiological and genetic research have improved our understanding of this condition and randomized prospective trials are being planned to determine the intervention strategies, which will optimize quality of life and long-term well-being. The International Menopause Society has commissioned a number of experts at the forefront of their specialty to define the state of the art in the understanding of this condition, to advise on practical management strategies, and to propose future research strategies. It is hoped that a global task force will subsequently be convened in order to formulate a consensus statement across key societies, to accelerate date collection and analysis of a global POI registry, and to facilitate progress in the key defined areas of research.